ANALYSIS OF FACTORS THAT AFFECTING INTEREST IN SAVING AT BANK MUAMALAT KCP BOYOLALI (STUDY ON GENERATION Z OF BOYOLALI REGENCY) - Kurnianingsih, Mutiara Dwi; Setiawan, Agus (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research Aims: This study aims to examine the influence of financial literacy, trust, promotion, and perception of religiosity on Generation Z's interest in saving at Bank Muamalat Sub-Branch Boyolali, Central Java, Indonesia. Design/Methodology/Approach: This research adopts a quantitative correlational approach with a descriptive-verifiable design. Data were collected through an online questionnaire using a purposive non-probability sampling technique, targeting 400 Generation Z respondents in Boyolali Regency. The collected data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Research Findings: The findings indicate that promotion and perception of religiosity have a positive and significant effect on saving interest. In contrast, financial literacy and trust do not significantly influence Generation Z's intention to save in Bank Muamalat. The results suggest that promotion and religious values are the main drivers of saving behavior among Gen Z in this context. Theoretical Contribution/Originality: This study contributes to the Islamic banking literature by integrating four variables rooted in the Theory of Planned Behavior (TPB) within a single empirical model. It highlights the unique role of religiosity in shaping financial decisions among youth in a religiously-oriented region, offering novel insights into value-based financial behavior. Practitioners/Policy Implications: The results recommend that Bank Muamalat optimize its digital and community-based promotional strategies and strengthen the integration of religious values in financial services to increase Gen Z engagement. Tailoring marketing efforts to their digital preferences and moral considerations can effectively enhance saving interest. Research Limitations/Implications: The use of purposive sampling and online data collection may limit the generalizability of findings due to potential self-selection and social desirability biases. Future research should employ probability sampling and explore additional variables such as digital service quality, peer influence, and fintech preferences to enrich understanding of Gen Z's financial behavior in Islamic banking.